2014
DOI: 10.1016/j.autneu.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic remodeling of the guinea pig intrinsic cardiac plexus induced by chronic myocardial infarction

Abstract: Myocardial infarction (MI) is associated with remodeling of the heart and neurohumoral control systems. The objective of this study was to define time-dependent changes in intrinsic cardiac (IC) neuronal excitability, synaptic efficacy, and neurochemical modulation following MI. MI was produced in guinea pigs by ligation of the coronary artery and associated vein on the dorsal surface of the heart. Animals were recovered for 4, 7, 14, or 50 days. Intracellular voltage recordings were obtained in whole mounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…In the porcine model, chronic ventricular infarction is accompanied by similar changes in somata of the stellate ganglia (SG) (Ajijola et al, 2015). In agreement with such histological evidence, i n vitro intracellular studies of IC neurons derived from chronic MI animals have demonstrated enhanced neuronal excitability, altered synaptic efficacy, and adaptive reorganization of neurochemical phenotypes and neuromodulation within the intrinsic cardiac nervous system (Hardwick et al, 2014; Hardwick et al, 2008). In fact, it is becoming evident that the ICNS, as the final integrator of cardiac neuraxial control, can undergo significant reorganization – both anatomical and functional – during the evolution of chronic MI (Rajendran et al, 2016).…”
Section: Introductionmentioning
confidence: 60%
“…In the porcine model, chronic ventricular infarction is accompanied by similar changes in somata of the stellate ganglia (SG) (Ajijola et al, 2015). In agreement with such histological evidence, i n vitro intracellular studies of IC neurons derived from chronic MI animals have demonstrated enhanced neuronal excitability, altered synaptic efficacy, and adaptive reorganization of neurochemical phenotypes and neuromodulation within the intrinsic cardiac nervous system (Hardwick et al, 2014; Hardwick et al, 2008). In fact, it is becoming evident that the ICNS, as the final integrator of cardiac neuraxial control, can undergo significant reorganization – both anatomical and functional – during the evolution of chronic MI (Rajendran et al, 2016).…”
Section: Introductionmentioning
confidence: 60%
“…The lack of regionality in neural remodeling from left and right-sided MI may reflect a difference in how afferent (transduction of signals following an MI) and efferent sympathetic activation reach the heart. A more important explanation is that the intrinsic cardiac network (ICN) 18 is the primary site transducing cardiac injury to the CNS, and subsequent distribution of remodeling-inducing signals to both stellate ganglia 19, 20 via increased sympathetic outflow. Whether there is differential remodeling in the ICN to left and right-sided MI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The massive sensory and ischaemic trauma associated with myocardial infarction (MI) induces dynamic morphological and phenotypic remodelling of the intrinsic cardiac nervous system, not limited to the infarcted region [25]. A ‘neural sensory border zone’ of infarction appears, with those afferents within the infarcted region becoming less sensitive, and those in the border and remote regions preserved or enhanced [57].…”
Section: Introductionmentioning
confidence: 99%